Coordination of the hemilabile ligand diphenylvinylphosphine to Ru4(µ-H)4(CO)12: synthesis, stability and structural studies - Neo, Edward Ren Kai (2022)
The tetraruthenium tetrahydrido carbonyl cluster Ru4(µ-H)4(CO)12 (1) reacts with diphenylvinylphosphine under thermal activation to give the substitution products Ru4(µ-H)4(CO)12−n(κ1-Ph2PCH=CH2)n, (2) (n = 3 (a); 4 (b)). Both 2a and 2b have been completely characterized, including by single-crystal X-ray diffraction analysis. Each of the diphenylvinylphosphine ligands in 2a and 2b is terminally bound, via the phosphorus atom, to a different ruthenium metal center, while the hydride positions in the Ru4(µ-H)4 cores retain the D2d symmetry of the parent cluster 1. Clusters 2a and 2b were able to retain their structural integrity at elevated temperatures. Graphic Abstract: Thermolysis of Ru4(μ-H)4(CO)12 (1) in cyclohexane with diphenylvinylphosphine afforded the tri- and tetra-substituted derivatives Ru4(μ-H)4(CO)9(κ1-Ph2PCH=CH2)3 (2a) and Ru4(μ-H)4(CO)8(κ1-Ph2PCH=CH2)4 (2b). For both substituted clusters, the diphenylvinylphosphine ligands are bound terminally to the tetraruthenium core via the phosphorus atoms while the hydride positions retain the D2d symmetry of the parent cluster 1.[Figure not available: see fulltext.]